A Clinical-Based Drug Interaction Alert (CIDIA) System for Preventing Drug Interaction and Its Associated Factors at Rural Primary Care Centres - Sari, Flori R; Anwar, Saiful; Risahmawati, -; Fadhilah, Marita; Ekayanti, Fika (Bangladesh Journal of Medical Science, 2023)
Objectives: Drug-drug interaction (DDI) occurs following the prescription of more than one drug. DDI and its associated factors in Indonesia’s country’s primary care have not been reported. Materials and Methods: Through this descriptive cross-sectional study, we analysed the DDI incidence using the Clinical-Based Drug Interaction Alert (CIDIA) alert system. Purposive research was carried out by analysing prescriptions (n=2410) from nine primary health cares. Results: CIDIA alert system detected 7.5% DDI incidence in all prescriptions, categorized as mild (63%), moderate (36%) and serious (1%). Significant DDI incidence was observed in female patients (p<0.01), in patients older than 18 years (p<0.01) and in patients receiving three or more drugs (p<0.01). The most frequent incidence of DDI from each category was paracetamol-domperidone; dexamethasone-mefenamic acid and captopril-allopurinol. Conclusion: CIDIA alert system has been shown to provide beneficial support in detecting DDI incidence. Careful consideration should be addressed particularly towards female patients, older patients, and patients receiving three or more drugs in preventing DDI incidence. Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 667-675